PENGARUH MODEL COOPERATIVE INTEGRATED READING AND COMPETITION TERHADAP KEMAMPUAN MENGANALISIS TEKS CERPEN SISWA KELAS XI SMA NEGERI 1 TALAWI - Sari, Rafika Muspita; Karimaliana, Karimaliana; Nasution, Susi Masriani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The purpose of this study was to determine the effect of the Cooperative Integrated Reading And Competition model on the Ability to Analyze Short Story Texts of Class XI of SMA Negeri 1 Talawi in the 2024/2025 Academic Year. This type of research is Experimental research. The sample in this study was class XI-2 as a control class using the Cooperative Integrated Reading And Competition Model and class XI-3 as an experimental class using conventional methods. After the learning was completed, a post-test was obtained with an average result of the experimental class of 80 (good category) and the control class of 61.9 (sufficient category). The results of the to calculation that have been obtained show that the t value is obtained, then consulted with the t table at the 5% and 1% levels with df = (N1 + N2) -2 = (36 + 36) -2 = 70. The t-table with df = 70 yields a significance level of 5% = 2.00 and a significance level of 1% = 2.65 because the calculated t (to) is greater than the t-table (t1), i.e., a significance level of 5% (6.93>2.00). Therefore, the significance level of 1% (6.93>2.65) means the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This indicates that the experimental class performed better in learning to analyze short stories than the control class. Therefore, the alternative hypothesis, namely that there is a significant influence of the Cooperative Integrated Reading and Competition model on the ability to analyze short stories in grade XI of SMA Negeri 1 Talawi in the 2024/2025 academic year, is accepted.Keywords: model, learning, short story textAbstrak: Tujuan penelitian ini adalah untuk mengetahui pengaruh model Cooperative Integrated Reading And Competition terhadap Kemampuan Menganalisis Teks Cerpen Kelas XI SMA Negeri 1 Talawi Tahun Ajaran 2024/2025. Jenis penelitian ini adalah penelitian Eksperimen. Sampel dalam penelitian ini yaitu kelas XI-2 sebagai kelas kontrol dengan menggunakan Model Cooperative Integrated Reading And Competition dan kelas XI-3 sebagai kelas eksperimen dengan menggunakan metode konvensional. Setelah pembelajaran selesai diberikan, diperoleh post-test dengan hasil rata-rata kelas eksperimen 80 ( kategori baik) dan kelas kontrol 61,9 (kategori cukup). Hasil perhitungan to yang telah diperoleh yakni menunjukkan bahwa nilai t diperoleh, selanjutnya dikonsultasikan dengan ttabel pada taraf 5% maupun 1 % dengan dk = (N1+N2) -2 = (36+36)-2=70. Pada tabel t dengan dk =70 diperoleh taraf signifikan 5% = 2,00 dan taraf signifikan 1% = 2,65 karena thitung (to) lebih besar dari ttabel (t1), yakni taraf signifikan 5% (6,93>2,00). Maka taraf signifikan 1% (6,93>2,65), maka hipotesis nihil (Ho) ditolak dan hipotesis alternative (Ha) diterima. Hal ini berarti dalam pembelajaran menganalisis teks cerpen kelas eksperimen lebih baik dibandingkan dengan kelas kontrol. Maka artinya hipotesis alternatif yaitu ada pengaruh yang signifikan dengan model Cooperative Integrated Reading And Competition terhadap kemampuan menganalisis teks cerpen kelas XI SMA Negeri 1 Talawi Tahun Ajaran 2024/2025 diterima.Kata kunci : model, pembelajaran, teks cerpen